KERJASAMA INDONESIA DENGAN AUSTRALIA DALAM KEAMANAN SIBER - ., Afifah; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Cybersecurity is one of the efforts to protect and maintain national security from treats that can damage due to the development of globalization which is marked by technological advances and digital connectivity between countries so that it has a risk of spreading cybercrime across countries. The research uses descriptive qualitative methods with data collection techniques carried out through document analysis based on sources obtained from official government documents, news, and journal articles related to cybersecurity cooperation. This research uses cyber diplomacy theory to explain cooperation efforts for cybersecurity in both countries. The results showed that Indonesia and Australia cooperated as an effort to improve the national interests of each country in the form of increasing the security of Indonesia and Australia and the Indo-Pacific region, and also as an effort to strengthen relations between the two countries. Keywords: Bilateral Cooperation, Cyber Security, Indonesia, Australia, Cyber Crime